Comparative Analysis between SA-516 Gr 70 Material with SA-537 Class 2 Material in Shell Pressure Vessel Fabrication Process - Puspita, Widya Rika; Putri, Sarah Athaullah Wenna; Jefiza, Adlian; Arifin, Muhammad; Maulidah, Hana Mutialif; Nakul, Fitriyanti; Suciningtyas, Ika Karlina Laila Nur; Putra, Irwanto Zarma; Budiana, Budiana; Futra, Asrizal Deri; Wivanius, Nadhrah (JURNAL INTEGRASI, 2024)
A pressure vessel is a container designed to hold fluids under pressure, including liquids and gases with varying pressures and temperatures. The pressure exerted on the vessel's walls and body is a critical factor that must be carefully considered to ensure compliance with applicable international design standards and prioritize worker safety and security. This research focused on a pressure vessel to investigate the impact of temperature on shell thickness to meet ASME standards. The study utilized shell components made from SA-516 Gr 70 and SA-537 materials. Experiments were conducted with each material at temperatures of 250°C, 235°C, and 343°C, revealing that thickness varies based on material and temperature. The research findings demonstrate compliance with ASME standards, as the shell thickness in all trials exceeded the minimum specified in the drawings.